PPO.18 Morph or Measure? Pregnancy Outcome Related to Five Different Indices of Body Shape and Size in Women – Feasibility Study. (9th June 2014) - Bentham, GL; Goyder, K; Jeffreys, A; Medd, E; Liebling, R
Abstract : Aims/Objectives: We aim to establish which measure of obesity is most useful in predicting mode of delivery. Background: Obesity is a major risk factor for adverse events in pregnancy. 'Body mass index' (BMI) has been the widely accepted measure of obesity. However, 'waist to hip ratio' (WHR) is thought to better reflect central adiposity. 1 If we are to identify obesity as a risk factor for adverse pregnancy and delivery outcome it is crucial that we explore different measures of obesity. Methods: We aimed to recruit all women who reached the inclusion criteria in two hospitals over a five-month period. Data was collected on demographics, BMI, thigh, hip and waist circumference. The primary outcome measure was mode of delivery, defined as either vaginal delivery or caesarean section. Results: We recruited 120 women to the study. Repeatability analysis demonstrated small mean differences (15 mm – 50 mm) between measurements. The best predictor of mode of delivery and emergency delivery (emergency caesarean and instrumental deliveries) was BMI and waist measurement (see graphs). Waist-hip ratio did not appear to correlate with mode of delivery. Summary and conclusions: This study has demonstrated that additional measurements were feasible and measurements were repeatable. There may be a suggestion that BMI or waist measurements are best predictors of mode of delivery. A larger study is planned to enable analysis of maternal and fetal antenatal complications. Reference: 1Yusuf S, Hawken S, Ounpuu S, Bautista L, Franzosi MG, Commerford P, et al . Obesity and the risk of myocardial infarction in 27, 000 participants from 52 countries: a case-control study. Lancet. 2005;366:1640–9